2019
DOI: 10.1007/s00167-019-05349-x
|View full text |Cite
|
Sign up to set email alerts
|

The development of the anterior cruciate ligament in the paediatric population

Abstract: PurposeThe aim of this study was to retrospectively compile normative data on the anterior cruciate ligament (ACL) in the paediatric population with magnetic resonance imaging, emphasizing the differences between men and women. MethodsIn this retrospective study, musculoskeletal radiologists evaluated length, area, coronal and sagittal inclination of the ACL and inclination of the intercondylar notch. A total of 253 MR examinations (130 males and 123 females between 6 and 18 years of age) were included. The as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 33 publications
6
19
1
Order By: Relevance
“…Our findings regarding the growth of the ACL suggest that there are age-specific changes in the geometric proportions of the tissue throughout skeletal growth in the pig model, and that the growth of the ACL does not parallel growth in the other tissues. Similarly, previous studies have shown that the CSA of the human ACL increases in size up to 10–12 years of age but halts in growth prior to the end of overall skeletal growth [8, 31]. Additional studies comparing the growth of the human ACL to muscles surrounding the knee have shown more rapid growth in the ACL halting prior to the end of muscle growth [32].…”
Section: Discussionmentioning
confidence: 72%
“…Our findings regarding the growth of the ACL suggest that there are age-specific changes in the geometric proportions of the tissue throughout skeletal growth in the pig model, and that the growth of the ACL does not parallel growth in the other tissues. Similarly, previous studies have shown that the CSA of the human ACL increases in size up to 10–12 years of age but halts in growth prior to the end of overall skeletal growth [8, 31]. Additional studies comparing the growth of the human ACL to muscles surrounding the knee have shown more rapid growth in the ACL halting prior to the end of muscle growth [32].…”
Section: Discussionmentioning
confidence: 72%
“…31; 32 The female porcine ACL increases in length, CSA, and angular orientation throughout skeletal growth 22; 23 , similar to humans. 58; 33 These studies also revealed age-specific differences in growth and function of the AM and PL bundles. 23 However, these findings leave open the question of whether functional maturation of the ACL and its bundles is sex-specific.…”
Section: Introductionmentioning
confidence: 78%
“…The ACL is similar in size between males and females during childhood, but becomes larger in length and cross-sectional area (CSA) in males after the onset of adolescence. [5][6][7][8] Additionally, anterior-posterior (AP) knee laxity decreases throughout skeletal growth with similar values between males and females during childhood. [9][10][11] During adolescence [9][10][11] and adulthood, 12 AP knee laxity appears greater in females than males.…”
Section: Introductionmentioning
confidence: 99%
“…We do know that the ACL appears to sustain pronounced growth up to the age of 10 to 12 years, after which the ACL surface area and volume stabilize. 23,40 We do not know, however, how catabolic mechanisms might affect the ACL and its development or where the threshold between anabolic and catabolic factors lies. As with other tissues, 27,34 significant catabolic processes most likely start to occur when the rate of degradation exceeds the rate of synthesis, but these processes are unknown in the ACL.…”
Section: Discussionmentioning
confidence: 99%